A certain gamble: Institutional change, leader turnover, and their effect on rivalry termination. (May 2023) - Saunders, Richard J
Previous research shows that leader turnover and change in a leader's winning coalition are associated with rivalry termination. However, this research often conflates change in leadership or winning coalition with more fundamental reform of the institutions governing the state. This article argues that only changes in a rival's governing institutions should lead to rivalry termination. Changes in leader preferences may lead to conciliatory policies, but provide no certainty regarding the sincerity or longevity of these policies. Fundamental changes to the institutions of a state alter the menu of policy options available to the leadership and are difficult to undo. Institutional reform in Rival A makes the leadership of Rival B more willing to undertake potentially risky cooperative action, leading to rivalry termination. I test this argument in a dataset of rivalry terminations spanning 1919–2010, finding that institutional reform in one rival leads to an increase in the likelihood of rivalry termination regardless of the issues of contention. Irregular leader turnover and change in a state's winning coalition have no effect. Further, in a break with previous research, I find that any institutional reform—toward autocracy, toward democracy or laterally—is associated with an increased likelihood of rivalry termination.